Assessment of the Performance of 210Pb-Based Dating Models with a Challenging Sediment History in Maryport Harbour (UK) - José M. Abril-Hernández (Journal of Marine Science and Engineering)
The 210Pb-based method is used for absolute age determination in recent sediments (<150 years). Different assumptions are possible, leading to different models and chronologies. The evaluation of the capacities and limitations of the models in challenging sedimentary scenarios is of broad interest to the scientific community, and this is the aim of the present work. The performance of the classical models, CFCS and CRS, and the novel TERESA is assessed with a 2 m long, high-resolution core sampled in Maryport Harbour, UK, by using raw data from the literature. It was affected by dredging, shortening, and by the anthropogenic impacts of radionuclides released by the Sellafield nuclear plant and the phosphate industry in Whitehaven and was considered non-datable by the 210Pb method. A reference chronology from Sellafield-derived radionuclides serves to assess the 210Pb dating models. The study uses the mass depth scale and solves the estimation of the unsupported fraction of 210Pb needed for the models. The profile was very irregular, and a cluster analysis led to an ambiguous use of the piecewise CFCS model. The inventory was incomplete and in an unsteady state, but the CRS model can be tentatively applied with the reference SAR and the reference date methods, although also with ambiguous results. TERESA can explicitly handle 210Pbexc fluxes and sedimentation rates that vary over time and shows the best performance with insightful outputs.